TESL students' test taking approaches and perceptions of the Malaysian University English Test (MUET) / Nor Hafeez Norizam - Norizam, Nor Hafeez (2014)
MUET was introduced with the aim to improve Malaysian students' level of English proficiency. Despite being in place for 15 years, recent end-year MUET result has painted an alarming exposure of the true level of Malaysians students' English proficiency. Test-takers' achievement in MUET can be attributed to two factors: the test-takers' perceptions of the examination and test-taking approaches in the examination. However, these two factors are being underinvestigated and the scarcity of researches conducted in Malaysia suggests a need for such a study. The present study is aimed to explore the test-taking approaches and the perceptions of MUET among TESL students in UiTM. Descriptive statistical analysis was employed to examine the two aforementioned factors. The data was collected through the survey method using questionnaires as the instrument. 30 Semester Eight B. Ed. TESL students (16 males and 14 females) participated in the study. Results showed that the TESL students practised positive test-taking approaches in MUET. However, the TESL students' perceptions of MUET were mixed and divided between positive and negative. Some important implications and recommendations have been brought forward from this study to be used in prospective revision of MUET in the future.